'Not Reading Just Seems Crazy to Me': Religious Youths’ Textual Ideologies of Sacred Texts - Rackley, Eric (Language and Literacy / Langue et littératie, 2024)
This study examines six Latter-day Saint youths’ textual ideologies of sacred texts. Inductive analyses point to three shared textual ideologies related to youths’ expectations about (a) the educative nature of sacred texts, (b) the relevance sacred texts had in their lives, and (c) the amount of time they should spend reading them. Findings support and extend existing language and literacy research by providing insights into the social and cultural forces that shape how religious youth engage with and use sacred texts. Implications of this work offer paths for future literacy research and practice.